How do recycled concrete aggregates modify the shrinkage and self-healing properties?. (February 2018) - Medjigbodo, Sonagnon; Bendimerad, Ahmed Z.; Rozière, Emmanuel; Loukili, Ahmed
Abstract: This paper presents the main results of a research carried out to analyze the mechanical properties, intrinsic permeability, drying shrinkage, carbonation, and the self-healing potential of concrete incorporating recycled concrete aggregates. The recycled concrete mixtures were designed by replacing natural aggregates with 0%, 30%, and 100% of recycled concrete gravel (RG) and 30% of recycled concrete sand (RS). The water to equivalent binder ratio was kept constant and recycled concrete aggregates were initially at saturated surface dried (SSD) state. The contribution of the porosity of natural and recycled aggregates to the porosity of concrete was estimated to understand the evolution of the intrinsic permeability and the open porosity. At long term, the maximum variation of drying shrinkage magnitude due to recycled concrete gravels did not exceed 15%. The correlation between drying shrinkage and mass-loss through "drying depth" concept showed that recycled concrete aggregates are affected by drying as soon as concrete is exposed to desiccation. A good correlation between 1-day compressive strength and 18-month carbonation depth was observed. The recycled concrete aggregates presented a good potential for self-healing as the relative recovery of cracks reached up to 60%. Highlights: The effect of recycled concrete aggregates on the durability properties was investigated. Coarse recycled concrete aggregates had a limited influence on drying shrinkage. The drying depths of natural and recycled aggregates concretes were approximately the same. The recycled aggregates substitution showed a good potential of self-healing at long term.